NUTRITIONAL STRATEGIES FOR REDUCING SUGAR-SWEETENED BEVERAGE CONSUMPTION AND PREVENTING METABOLIC DISEASES - da Cruz, José Ribamar Sousa (Revista Sistemática, 2024)
Reducing the consumption of sugar-sweetened beverages is crucial for preventing and managing metabolic diseases such as obesity, insulin resistance, and type 2 diabetes. Excessive consumption of sodas and other sweetened beverages is a major risk factor for these conditions, as these drinks contain empty calories, exacerbating insulin resistance and causing harmful glycemic spikes. For patients with prediabetes, implementing effective nutritional strategies to reduce the consumption of these beverages is essential to prevent progression to type 2 diabetes. Nutritional interventions that promote awareness of the risks of sugar-sweetened beverages, offer healthy alternatives such as water and unsweetened teas, and modify the food environment are key to changing eating behaviors and improving metabolic health. Adopting a balanced diet rich in fiber and lean proteins is also important for controlling blood sugar levels and reducing cravings for sugary foods. Furthermore, combining nutritional strategies with regular physical activity can enhance the benefits, as exercise improves insulin sensitivity and contributes to weight management. Widely cited studies highlight the association between sugar-sweetened beverage consumption and an increased risk of type 2 diabetes and other chronic diseases. Public policies that encourage the reduction of sweetened beverage consumption are essential to combat the growing epidemic of metabolic diseases.